IMPLEMENTATION OF SLUM AREAS WITH DEVELOPMENT OF THEMATIC VILLAGES IN TANGERANG CITY - Aini Timur; Muhamad Busthomi; Endang Masduki (DIA: Jurnal Administrasi Publik, 2023)
In accelerating the handling of slum areas, the Government of Tangerang City continues to strive to improve infrastructure in order to reduce slum areas to become better areas. Various activities for handling slum areas have been carried out, one of which is through community empowerment with the development of thematic villages. This program is developed and utilized to support the improvement of people's welfare independently and sustainably by maximizing the potential of the region. This study aims to determine the implementation of handling slum areas using Charles O. Jones' theory with three aspects, namely organization, interpretation, and application. The research method was carried out using descriptive qualitative data collection techniques obtained through key informant interviews, document review and direct observation, with data sources obtained from primary and secondary data with loci in Mango Village and Pinkli Village. The strategy for handling slum areas in Tangerang City has been carried out comprehensively and partially and has begun to have an impact on the surrounding community. However, this is still being carried out on an ongoing basis so that the City of Tangerang becomes a city that is livable, investable, visitable, and an e-city.